Mechanical reinforcement of electrospun poly(vinyl alcohol) by α‐FeOOH nanowires. Issue 7 (20th October 2016) - Šutka, Anna; Järvekülg, Martin; Šutka, Andris; Heinmaa, Ivo; Mäeorg, Uno; Smits, Krisjanis; Timusk, Martin
Abstract : We report the mechanical performance of α‐FeOOH nanowire reinforced poly(vinyl alcohol) (PVA) composite nanofiber mat, fabricated using straightforward aqueous processing methods. Goethite (α‐FeOOH) nanocrystals have a high elastic modulus and –OH rich surface, ensuring strong interactions with hydrophilic polymers and effective reinforcement. Needle‐less electrospinning resulted in alignment of the nanowires along fibre axis, as confirmed by transmittance electron microscopy studies. Produced composite PVA nanofibers containing 10 wt% goethite nanoparticles exhibited an outstanding fivefold increase in Young's modulus and 2.5‐fold improvement of tensile strength compared to mats of neat PVA. The addition of α‐FeOOH had a significant influence on glass transition temperature indicating formation of interphase regions around nanowire inclusions. Observed properties are explained by nanowire grafting in the precursor solution, extensive interactions between the adsorbed PVA chains and the matrix and percolation of interphase regions at 10 wt% α‐FeOOH. POLYM. COMPOS., 39:2461–2468, 2018. © 2016 Society of Plastics Engineers